2022
DOI: 10.1038/s41598-022-23032-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of patients with polypharmacy in adult population from Korea

Abstract: Polypharmacy and its rising global prevalence is a growing public health burden. Using a large representative nationwide Korean cohort (N = 761,145), we conducted a retrospective cross-sectional study aiming to identify subpopulations of patients with polypharmacy and characterize their unique patterns through cluster analysis. Patients aged ≥ 30 years who were prescribed at least one medication between 2014 and 2018 were included in our study. Six clusters were identified: cluster 1 mostly included patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…Our lower numbers could point to a more appropriate and safe use of drugs by these patients and a more suitable prescription of medications by the healthcare professionals in the Community of Madrid [ 42 ]. In a similar way, the rates of hospitalizations were lower than those observed in many previous reviews [ 13 , 27 , 42 , 44 ], although similar [ 32 ] or lower [ 25 ] to others. In comparison with the total population of the Community of Madrid, patients with polypharmacy visited the emergency room and were hospitalized around two times more [ 29 ], coinciding with the results reported by Nascimento et al [ 13 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our lower numbers could point to a more appropriate and safe use of drugs by these patients and a more suitable prescription of medications by the healthcare professionals in the Community of Madrid [ 42 ]. In a similar way, the rates of hospitalizations were lower than those observed in many previous reviews [ 13 , 27 , 42 , 44 ], although similar [ 32 ] or lower [ 25 ] to others. In comparison with the total population of the Community of Madrid, patients with polypharmacy visited the emergency room and were hospitalized around two times more [ 29 ], coinciding with the results reported by Nascimento et al [ 13 ].…”
Section: Discussionsupporting
confidence: 78%
“…The most prevalent comorbidities within the polypharmacy population were hypertension, dyslipidaemia, diabetes, osteoporosis, dysrhythmias, arthrosis and obesity, in accordance with other populations with polypharmacy [ 13 , 19 , 27 ] and with the elderly population with polypharmacy [ 12 , 15 , 18 , 21 , 24 26 , 28 ]. Our results agree with earlier findings that cardiovascular diseases are more prevalent in men, while arthritis, osteoporosis and thyroid disorder are more prevalent in women [ 12 , 15 , 16 , 18 , 26 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Initiatives to reduce potentially inappropriate medication use, especially among frail older adults living in long-term care facilities, should be prioritized. Considering that patients with polypharmacy usually visit multiple medical institutions in Korea, it may be an option to implement a primary care physician system for older patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies primarily investigated polypharmacy issues in populations other than pregnant women. [11][12][13] Although some studies showed a trend of polypharmacy in pregnant women, they were either not nationally representative or focused on specific conditions such as psychiatric illnesses, epilepsy, and migraines. [14][15][16][17] Therefore, findings from previous studies cannot provide a comprehensive overview of polypharmacy in pregnant women from a US nationally representative perspective.…”
Section: Introductionmentioning
confidence: 99%